Chagas disease and transfusion medicine: a perspective from non-endemic countries - Angheben, Andrea (Blood Transfus, 2015)
In the last decades, increasing international migration and travel from Latin America to Europe have favoured the emergence of tropical diseases outside their “historical” boundaries. Chagas disease, a zoonosis endemic in rural areas of Central and South America represents a clear example of this phenomenon. In the absence of the vector, one of the potential modes of transmission of Chagas disease in non-endemic regions is through blood and blood products. As most patients with Chagas disease are asymptomatic and unaware of their condition, in case of blood donation they can inadvertently represent a serious threat to the safety of the blood supply in non-endemic areas. Since the first cases of transfusion-transmitted Chagas disease were described in the last years, non-endemic countries began to develop ad hoc strategies to prevent and control the spread of the infection. United States, Spain, United Kingdom and France first recognised the need for Trypanosoma cruzi screening in at-risk blood donors. In this review, we trace an up-to-date perspective on Chagas disease, describing its peculiar features, from epidemiological, pathological, clinical and diagnostic points of view. Moreover, we describe the possible transmission of Chagas disease through blood or blood products and the current strategies for its control, focusing on non-endemic areas.